Simulasi Penggunaan Lahan Untuk Kelestarian Bendung Bila pada Sub Das Bila Propinsi Sulawesi Selatan - Sitti Nur Nur Faridah; Totok Prawitosari (Jurnal Keteknikan Pertanian, 2008)
The optimal land use system in Bila sub-watershed is the land use system that can give erosion contribution rate below or minimally equal to the Tolerable Soil Loss (TSL) value of Bila sub-watershed soil. The erosion factors are determined by parameter : R (rain erosivity), K (soil erodibility),: LS (topography), C (land coverage), and P (land conservation). Each parameter is overlaid, than it is evaluated in each land unit in Bila sub-watershed. The acquired data is processed by using Geographic Information System (GIS) supported with Arc View program and Microsoft Word and Microsoft Excel softwares. The qualified erosion and sediment rate values obtained from simulation result which is meet the standard for erosion and sediment control and management in Bila sub-watershed area and Bi/a weir were 10,597 tonnes/ha/yearand 50,864 m3/km2/year respectively. Keywords: ---Diterima: 3 Oktober 2007; Disetujui: 25 Pebruari 2007